2019
DOI: 10.2174/1389201020666190314125534
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms Isolated from Stored Meat in India, with Potential Antimicrobial Activity against Food Pathogens

Abstract: Background: World Health Organization has estimated that 1 in 10 people fall ill and 4, 20, 000 die every year from eating contaminated food. Food pathogens like Escherichia, Salmonella, Staphylococcus and Listeria pose a serious threat to human health. Objective: The objective was to isolate microbes from meat stored at refrigerated conditions and evaluate the antimicrobial activity of the cell-free supernatant against food pathogens. Methods: Chicken and Pork samples were procured and stored at refrigera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Additionally, they have shown antimicrobial activities against pathogenic bacteria, such as Salmonella enterica subsp. enterica serovar Typhimurium and Listeria monocytogenes 46 , 47 . On the other hand, Ln.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they have shown antimicrobial activities against pathogenic bacteria, such as Salmonella enterica subsp. enterica serovar Typhimurium and Listeria monocytogenes 46 , 47 . On the other hand, Ln.…”
Section: Discussionmentioning
confidence: 99%
“…[29] has been reported in pork meat samples from retail markets. These bacterial species are considered a real danger to human health [30].…”
Section: Prevalence Of Foodborne Bacteria In Raw Pork and Beef Meatmentioning
confidence: 99%
“…2 Percentage in relation to total number of positive samples(25). 3 Percentage in relation to total number of collected samples(30)…”
mentioning
confidence: 99%
“…Previously, Leuconostoc spp. have been isolated from chicken and pork samples from Indian (Thangavel et al, 2019) which showed promising results against E. coli , L. monocytogenes , Staphylococcus aureus and S. Typhimurium. The objective of the present study was to evaluate the efficacy of the Leuconostoc isolates in controlling E. coli and L. monocytogenes in spinach stored at 4°C for a period of 5 d.…”
Section: Introductionmentioning
confidence: 99%